2020
DOI: 10.1002/arch.21735
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile analysis of circular RNAs in BmN cells (Bombyx mori) upon BmNPV infection

Abstract: The disease caused by Bombyx mori nucleopolyhedrovirus (BmNPV) has always been difficult to control, resulting in tremendous economic losses in the sericulture industry. Although much has been learned about the impact of noncoding RNAs on pathogenesis, the role of circular RNA (circRNA) in insect immunity remains unclear. To explore circRNA regulation involved in BmNPV infection, we used transcriptome analysis of BmN cells with or without BmNPV infection to generate circRNA data set. A total of 444 novel circR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…The above characteristics suggested that circRNAs in Ae . albopictus were similar to those identified in other insect species [ 17 19 , 67 ], and some circRNAs were even conserved between mosquitoes and fruit flies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The above characteristics suggested that circRNAs in Ae . albopictus were similar to those identified in other insect species [ 17 19 , 67 ], and some circRNAs were even conserved between mosquitoes and fruit flies.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, the highly expressed circRNAs in Drosophila [66] were also present in our circRNA-seq data, and further RT-PCR amplification followed by Sanger sequencing using divergent primers confirmed the existence of the predicted BSJ (S5E-S5H Fig) . The above characteristics suggested that circRNAs in Ae. albopictus were similar to those identified in other insect species [17][18][19]67], and some circRNAs were even conserved between mosquitoes and fruit flies.…”
Section: Plos Pathogenssupporting
confidence: 73%
“…B. mori nucleopolyhedrovirus (BmNPV) causes diseases that have always been difficult to control, resulting in tremendous economic losses in the sericulture industry [ 83 , 84 ]. It has been proposed that BmNPV proliferation within host cells is mediated by a cascade of viral gene expression, and identifying host genes that respond to BmNPV infection is a promising strategy for developing BmNPV-resistant silkworms [ 85 , 86 ].…”
Section: Circrnas In the Innate Immunity Of Insectsmentioning
confidence: 99%
“…It has been proposed that BmNPV proliferation within host cells is mediated by a cascade of viral gene expression, and identifying host genes that respond to BmNPV infection is a promising strategy for developing BmNPV-resistant silkworms [ 85 , 86 ]. Despite this, several recent studies have investigated the effect of circRNA involvement in BmNPV infection [ 81 , 84 , 87 ]. It has been demonstrated that after BmNPV infection, the expression levels of circRNAs in the silkworm midgut are altered, and these dysregulated circRNAs may play roles in BmNPV infection, implying that these altered circRNAs may be a novel type of anti-viral factor [ 88 ].…”
Section: Circrnas In the Innate Immunity Of Insectsmentioning
confidence: 99%